2007
DOI: 10.1248/cpb.55.985
|View full text |Cite
|
Sign up to set email alerts
|

Submicron Particles of SBA-15 Modified with MgO as Carriers for Controlled Drug Delivery

Abstract: Controlled drug delivery technology represents one of the most rapidly advancing areas of biomedical science contributed by chemists and chemical engineers to health care. Controlled delivery systems offer significant advantages over conventional dosage forms, in terms of enhanced efficiency of medicine, and improved patient compliance and convenience over as the efficiency of medicine. The method by which a drug is delivered can have a significant effect on its therapeutic efficacy. The controlled drug releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…4) of ibuprofen depicted a typical profile of a pure crystalline compound with a sharp endothermic peak (t peak at 79.04˚C, ΔH Fus 126.276 J/g) owing to its fusion and it complied with the reported data (Tayade and Kale, 2004;Shen et al, 2007). …”
Section: Differential Scanning Calorimetry Analysissupporting
confidence: 80%
“…4) of ibuprofen depicted a typical profile of a pure crystalline compound with a sharp endothermic peak (t peak at 79.04˚C, ΔH Fus 126.276 J/g) owing to its fusion and it complied with the reported data (Tayade and Kale, 2004;Shen et al, 2007). …”
Section: Differential Scanning Calorimetry Analysissupporting
confidence: 80%
“…Among the oxide compounds, magnesium oxide (MgO) has interesting properties and is employed in industrial applications [11][12][13][14][15][16][17][18][19][20]. In 1961, Coble investigated the effect of a small amount of magnesia on sintering of alumina for the first time and they reported that the adding of MgO less than 0.25 wt% led to obtaining a density near the theoretical The differential thermal analysis (DTA) of dried sol-gel product at 100 ∘ C for 24 hrs [22].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium oxide possesses interesting properties and potential applications in the areas such as pharmaceuticals [1], electrooptical devices [2], fluorescent displays [3], ferroelectric materials [4], etc. Magnesium oxide is also used in superconducting films as a substrate [5], and lithium ion batteries [6].…”
Section: Introductionmentioning
confidence: 99%